2016
DOI: 10.21767/2172-0479.100063
|View full text |Cite
|
Sign up to set email alerts
|

Activated Partial Thromboplastin Time, Prothrombin Time, Thrombin Time and Platelet Count Study in HIV Seropositive Subjects at Nnamdi Azikiwe Teaching Hospital Nnewi

Abstract: This study was aimed at evaluating the effect of HIV infection on hemostatic parameters, determination of the influence and duration of antiretroviral therapy (ART) on these parameters. It was carried out at the Nnamdi Azikiwe University Teaching Hospital, Nnewi. One hundred and eighty two subjects were recruited consisting; Sixty one (31 males and 30 females) HIV positive subjects on antiretroviral therapy (ART) with an ART duration of 6 months -2 years ≤5 years, ≤10 years; Sixty one (28 males and 33 females)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The aPTT value was also significantly higher in HIVinfected subjects (both on HAART and HAART naïve) than control subjects. The finding was in line with study done by Getawa and Adane [23], Abdollahi et al [24], Ifeanyichukwu et al [25] and Seyoun et al [26] Who reported that PT and aPTTwere significantly higher in HIV-infected adults than HIV-seronegative adults. The normal adult range of platelet count is 280 ±130 X 10 9 /l.…”
Section: Resultssupporting
confidence: 91%
“…The aPTT value was also significantly higher in HIVinfected subjects (both on HAART and HAART naïve) than control subjects. The finding was in line with study done by Getawa and Adane [23], Abdollahi et al [24], Ifeanyichukwu et al [25] and Seyoun et al [26] Who reported that PT and aPTTwere significantly higher in HIV-infected adults than HIV-seronegative adults. The normal adult range of platelet count is 280 ±130 X 10 9 /l.…”
Section: Resultssupporting
confidence: 91%
“…HAART containing protease inhibitor-1 is the combination regimen of HAART that has been widely reported to be associated with increased plasma levels of PAI-1 in HIV-infected individuals. 29 This finding is consistent with the Ifeanyichukwu et al, 31 and Seyoum et al, 29 studies in Nigeria who also found no effect of HAART duration on circulating PAI-1 antigen levels. Shortly after the introduction of HAART, there is a sharp suppression of viral replication with immune function rebuilding, and this is sustained in consistent and effective therapy.…”
Section: Coagulation and Fibrinolytic Markers Of The Hiv Participants...supporting
confidence: 85%
“…Participants were found to be on the first-choice antiretroviral drug combinations. A study by Ifeanyichukwu et al, 31 observed improvement in the coagulation profile in HIV infected individuals who were on the first line choice combination HAART. This suggests that these combinations of HAART could impact positively on the general haemostasis of people living with HIV/AIDS.…”
Section: Coagulation and Fibrinolytic Markers Of The Hiv Participants...mentioning
confidence: 99%
“…In contrast, Ephraim et al [26] reported that PT was significantly lower in subjects treated with ART compared to ART-naive (p < 0.0001) but platelet count was higher in the ART group (p > 0.05). The decrease in platelet count in HIV infection may be due to autoimmune destruction and thrombopoiesis disruption as a result of direct infection to megakaryocytes, as well as coagulopathy consumption in AIDS [1], [27].…”
Section: Discussionmentioning
confidence: 99%